Penilaian Livability Ruang Publik di Permukiman Padat Penduduk Studi Kasus Pada Ruang Publik di Permukiman RW 08 Kelurahan Lebak Siliwangi, Bandung - Irfan Irwanuddin; Alva F.P. Sondakh; Addina Nur Amalia; Dhienda Mariva (Unika Soegijapranata Semarang, 2019)
High-density settlement is frequently associated with a low value of quality of life. While in fact, there are other factors which strongly affecting this quality of life. One of those is liveability. When there is a public space in particular settlement region, the livability of this area will be affected accordingly. Meanwhile, the public space livability itself is constructed by two main factors, which are social factor and physical factor. The aim of this research was to evaluate livability value of public space in a study case settlement region located in RW 08 Kampung Lebak Siliwangi, Bandung. This study has done by carried out observations and interviews. The observation revealed the value of its physical attributes, while the interview revealed the value of its social attributes. This research has successfully met several findings. The case study is showing a relatively good livability value. Compared to the physical factor, social factor is showing a higher impact on increasing the livability value. ‘Facility’ became the most contributing variable among the physical factors, while ‘friendliness’ became the most contributing variable among the social factors.